2013
DOI: 10.1007/s10964-013-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Relationships, Parental Psychological Control, and Aggression: Maternal and Paternal Relationships

Abstract: Few studies have examined both maternal and paternal parenting practices in the prediction of child outcomes despite evidence that underscores the salience of fathers throughout their children's development. This study examined the role of the quality of mother-child and father-child relationships in buffering the influence of ineffective parenting practices on subsequent adolescent aggression. Measures of parental psychological control, the quality of the parent-child relationship, and youth aggressive behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 44 publications
3
57
0
Order By: Relevance
“…Although parental hostility is only one of several factors that render risk for increased aggressive behavior among adolescents, parental hostility is linked with a number of other factors also associated with risk (Farrington 2005). Thus, our findings likely extend to other domains of risk for aggressive behavior problems during adolescence such as low parental monitoring (Low et al 2012), psychological control (Murray et al 2014), and neighborhood and socioeconomic disadvantage (Karriker-Jaffe et al 2013). …”
Section: Discussionmentioning
confidence: 63%
“…Although parental hostility is only one of several factors that render risk for increased aggressive behavior among adolescents, parental hostility is linked with a number of other factors also associated with risk (Farrington 2005). Thus, our findings likely extend to other domains of risk for aggressive behavior problems during adolescence such as low parental monitoring (Low et al 2012), psychological control (Murray et al 2014), and neighborhood and socioeconomic disadvantage (Karriker-Jaffe et al 2013). …”
Section: Discussionmentioning
confidence: 63%
“…In a recent study, relationship quality was found to moderate the association between psychological control and aggression (Murray et al, 2013), such that maternal psychological control was predictive of higher rates of aggression when adolescents reported low-quality relationships with their father.…”
Section: Psychological Controlmentioning
confidence: 95%
“…Jordan, & Mercer, 2012), including depression (Barber, 1996;Mandara & Pikes, 2008;Plunkett et al, 2007;Soenens, Luyckz, Vansteenkiste, Duriez, & Goossens, 2008), anxiety (Drake & Ginsburg, 2012), academic achievement (Barber & Harmon, 2002), delinquency (Bradford, Barber, Olsen, Erickson, Ward, & Stolz, 2004), and aggression (Murray, Dwyer, Rubin, Knighton-Wisor, & Booth-LaForce, 2013). Considering the feelings of guilt, self-responsibility, dependency, low self-esteem, and depressed affect that often characterize the experience of psychological control (Barber, 1996), researchers have largely explored its relation to anxiety and depression.…”
Section: Psychological Controlmentioning
confidence: 99%
“…• Biological sex has long term implications for resilience in early adulthood (Chapple & Johnson, 2007;Masten, et al, 2004;Ribeaud & Eisner, 2010) • Early attachment has long term developmental implications for adaptive functioning in adulthood (Englund et al , 2011) • Punitive parenting practices have long term developmental implications regarding antisocial behavior (Villodas, et al, 2015) • SES has a significant impact on antisocial behaviors and coping in early adolescence (Garmezy et al , 1984;Kraus et al, 2011) • Close relationships with parents and friends in early adolescence are key to the development of problem solving skills (Casselman & Rosenbaum, 2014;Fergusson & Horwood, 2001 ;German et al, 2013;Masten & Tellegen, 2012;Murray et al, 2014;Newman, et al, 2007;Newton-Howes et al , 2015;Raby et al , 2015;Wang et al, 2013;Werner, 1996;1989;Zhang et al, 2015) • Mentorship though close relationships in early adolescence is crucial to the development of problem solving skills (Fruiht, 2015;Li & Yang, 2009;McKay, 2011) Given the observational nature of the present study and limited explained variance, the findings should be generalized with caution. However, it appears that resilience is a developmental construct that is relevant for many different populations including English speaking Canadians.…”
Section: Resultsmentioning
confidence: 99%
“…Murray et al (2014) examined the influence of father-child and mother-child relationships on aggression in adolescence. Results indicated that lower levels of female aggression were associated with higher quality parental relationships; however, this was not found to be true for male aggression in their sample.…”
Section: Early Adolescencementioning
confidence: 99%